2012
DOI: 10.1089/biores.2012.0270
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Elevation Down-Regulates β3 Integrin and Focal Adhesion Kinase and Inhibits Leptin-Induced Migration of MDA-MB-231 Breast Cancer Cells

Abstract: Breast cancer is one of the most common malignancies and a major cause of cancer death among women worldwide. The high mortality rate associated with breast cancer is mainly due to a propensity of the tumor to metastasize, even if small or undetectable. Given the relevant role of leptin in breast cancer growth and metastasis, novel strategies to counteract biological effects of this obesity-linked cytokine are warranted. Recently, we demonstrated that in MDA-MB-231 breast cancer cells, intracellular cAMP eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…Under the conditions used in our study, we find no significant effect of cAMP analogs or cAMP PDE inhibitors on proliferation of the breast cancer cells, indicating that the reduction of cell migration observed is functionally selective and not due to a lowering of cell numbers. Similar to these findings, another study also showed that forskolin significantly inhibited leptin-induced migration of MDA-MB-231 cells at levels in which it had no effect on cell proliferation [52].…”
Section: Discussionsupporting
confidence: 66%
“…Under the conditions used in our study, we find no significant effect of cAMP analogs or cAMP PDE inhibitors on proliferation of the breast cancer cells, indicating that the reduction of cell migration observed is functionally selective and not due to a lowering of cell numbers. Similar to these findings, another study also showed that forskolin significantly inhibited leptin-induced migration of MDA-MB-231 cells at levels in which it had no effect on cell proliferation [52].…”
Section: Discussionsupporting
confidence: 66%
“…cAMP also inhibits migration of highly invasive MDA‐MB‐231 cells (6, 7) and the expression of relevant proteins involved in breast cancer metastasis. These effects are mediated by both PKA‐ and Epac‐dependent pathways (30).…”
mentioning
confidence: 99%
“…Very surprisingly, we provided evidence that when cAMP levels are increased upon forskolin treatment, leptin drives cells toward apoptosis associated with a marked decrease of Bcl2 protein levels and accompanied by down‐regulation of protein kinase A (PKA). In addition, we also found that the inhibition by forskolin of leptin‐mediated cell migration is accompanied by a strong decrease of β3 integrin subunit and FAK protein levels (Naviglio et al, , 2010; Spina et al, , 2013). Overall, our above findings provide initial evidence of forskolin as a simple natural agent able to neutralize leptin‐induced oncogenic effects in breast cancer cells and extend the evidence for the potential efficacy of cAMP elevation in breast cancer therapy.…”
Section: Forskolin and Cancermentioning
confidence: 85%